Understanding Loyalty in a Company-Led Halal Brand Community: The Role of Perceived Benefit, Engagement, and Religiosity - Rahayu, Shafa; Lestari, Yuliani (Journal Integration of Management Studies, 2025)
Several brands nowadays, especially the Indonesian cosmetics industry, form a community managed by the company as a strategy to build customer loyalty. However, the effectiveness of this community in creating loyalty is still questionable. This study analyzes how perceived benefits, brand community engagement, and religiosity affect the repurchase intention of Wardah Youth Ambassador (WYA) members, with brand equity as a mediating variable. A quantitative approach was used through the distribution of an online questionnaire to 100 active members or alums of WYA. The data was analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Perceived benefits had a significant effect on brand equity and repurchase intent. Community engagement also had a significant effect on brand equity and repurchase intent. Religiosity affected brand equity, but had no direct effect on repurchase intent. Brand equity partially mediated the relationship between community engagement and repurchase intent. Joining a company-managed community does not necessarily create loyalty. Emotional and cognitive engagement, as well as value perceptions and religious alignment, play a key role in shaping the loyalty of Muslim Gen Z consumers. This research emphasizes the importance of meaningful and value-relevant brand experiences in maintaining customer loyalty.